Analisis Kandungan Arsenik (As) dan Cianida (CN) Depot Air Minum Isi Ulang di Kota Batam - Hazimah -; Nurlinda Ayu Triwuri (JURNAL REKAYASA SISTEM INDUSTRI, 2018)
Water is a fundamental and essensial need in life. Batam is one of industrial cities that use a lot of refill drinking water. Industry is a potential source of water pollution especially arsenic (As) and Cyanide (CN, it produces pollutants that are extremely harmful to people and the environment. Industry is a potential source of water pollution, it produces pollutants that are extremely harmful to people and the environment. Many industrial facilities use freshwater to carry away waste from the plant and into rivers, lakes and oceans. Inorganic industrial wastes are more difficult to control and potentially more hazardous Industries discharge a variety of toxic compounds and heavy metals. The most pollutans heavy metals are Lead,Cadmium, Copper, Chromium, Selenium, Mercury, Nickel, Zinc, Arsen and Chromium. Heavy metals are dangerous because they tend to bioaccumulate. While Cyanide is very harmful to the environment and other living things. The perpuse of this research is to know the content arsenic (As) and Cyanide (CN) in the depot of refill water in Batam. Sample analysis conducted at PT.Sucopindo branch Batam Riau Island-Indonesia. The sampel number of six samples from each district Batam is Salsabila Batam Center, Pak De Qua Tiban, Fun Qua batu Ampar, Fresh Qua Bengkong, Salwa Qua Batu Aji, dan Alam Qua Piayu. The result obtained Arsenic (As) and Cyanide (CN) content of sixth refills depots is <0,0001 mg/L dan <0,008 mg/L. The result of this research showed that all six samples meet the qualification of the Regulation of the Ministry of Health no.492 Year 2010 both arsenic (As) and cyanide (CN).